Balāgah al-Jasad al-Furjūwī baina al-Ta’bīr al-Ĥarakī wa al-Kalimah al-Manṭūqah Masraḥiyyah “Kharīf” Numūżajā - El Haouari, Yassine (Study Program of Arabic Language Teaching, 2024)
This research aims to analyze body rhetoric between motor expressions and spoken words in the play